MODEL PEMBELAJARAN KEWIRAUSAHAAN PADA PKBM BINAAN SKB KABUPATEN TEMANGGUNG - Azhar Azhar (Jurnal Kependidikan, 2011)
The study is aimed at describing the enterpreneurship learning model of the enterpreneurship training and the contribution of the education and training to enterpreneurship in the economic aspects. The study is conducted in the Community Learning Centre (CLC) in Temanggung regency. The study is qualitative research data are analysed by using the interactive analysis model. The subjects of the study are members of the CLC guided group. Research findings show that (1) The curriculum is developed on the basis of the needs of the course participants; learning activities include guided production, marketing, and independent entrepreneurship; emphasis is on trainees activities in business; and approaches are andragogic involving simulations and group discussions; (2) There is contribution from the training implementation toward the economic aspects in the form of earning increases in of the business units; and (3) There is contribution from the training implementation toward the increament of the knowledge and skills of the trainees as well as of the people in the surrounding